2014
DOI: 10.1002/app.41356
|View full text |Cite
|
Sign up to set email alerts
|

Tear force of physically crosslinked poly(vinyl alcohol) gels with different submicrometer‐scale network structures

Abstract: Poly(vinyl alcohol) (PVA) gels can be easily prepared by either the freeze‐thawing (FT gel) method or by the cast‐drying (CD gel) method. Although the resulting nanostructured networks of the FT and CD gels are similar, their physical properties are quite different; while CD gels are transparent and elastic, FT gels are opaque and less elastic. Moreover, the tear energy of the FT gels is much greater than that of the CD gels, which is a direct result of micrometer‐scale differences in their network structures.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Graphene nanoplatelet is defined as a flat monolayer of carbon atoms tightly packed into a two-dimensional (2D) honeycomb lattice. Thermally conductive fillers used with graphite (in this case, graphite nanoplatelets (GNP) and expanded graphite to form synergistic composites include carbon nanotubes, silicon carbide microparticles, and carbon fiber (CF) [67,68,79,80]. The development of synergistic polymer composites between CNTs and graphene has been conducted because of their higher thermal conductivity of 3000-6000 and 100-400 W/m.K, respectively.…”
Section: Thermal Conductivity Of Graphite and Other Conductive Fillersmentioning
confidence: 99%
See 3 more Smart Citations
“…Graphene nanoplatelet is defined as a flat monolayer of carbon atoms tightly packed into a two-dimensional (2D) honeycomb lattice. Thermally conductive fillers used with graphite (in this case, graphite nanoplatelets (GNP) and expanded graphite to form synergistic composites include carbon nanotubes, silicon carbide microparticles, and carbon fiber (CF) [67,68,79,80]. The development of synergistic polymer composites between CNTs and graphene has been conducted because of their higher thermal conductivity of 3000-6000 and 100-400 W/m.K, respectively.…”
Section: Thermal Conductivity Of Graphite and Other Conductive Fillersmentioning
confidence: 99%
“…The development of synergistic polymer composites between CNTs and graphene has been conducted because of their higher thermal conductivity of 3000-6000 and 100-400 W/m.K, respectively. It was reported by Yu et al [80] and Pak et al [81] that incorporating a small amount of carbon nanotubes (CNTs) with a high aspect ratio induced a synergistic enhancement in the thermal conductivity of composites by forming an effective 3D thermally conductive network. For instance, some researchers reported that the thermal conductivity of polycarbonate (PC) composite filled with 9.9 wt% expanded graphite and 0.1 wt% multi-walled carbon nanotubes (MWCNT) fillers was synergistically improved 49% when compared with pristine PC composite filled with 10 wt% EG alone [79].…”
Section: Thermal Conductivity Of Graphite and Other Conductive Fillersmentioning
confidence: 99%
See 2 more Smart Citations
“…PVA is a water-soluble polymer with wide practical application in a variety of fields, including wound dressing, implants, cell encapsulation, drug-delivery systems, soft contact lenses and dental applications, due to its excellent chemical resistance and physical properties, low toxicity and high biocompatibility [14][15][16] . An aqueous solution of PVA can form hydrogels through cast-drying process, where PVA physically cross links during the dehydration process 17 . In summary, the proposed approach facilitates facile, ondemand and cleanroom-free fabrication of microneedles with a desired geometry.…”
Section: Introductionmentioning
confidence: 99%